Analysis of Students' Level of Understanding of the Practice of Implementing Group Guidance and Counseling Services - Suryani, Rina; Pristanti, Nindya Ayu (An-Nadwah, 2024)
Group guidance and counseling services are fundamental competencies that must be mastered by prospective guidance and counseling (BK) teachers. This study aims to analyze the level of understanding of Medan State University students towards the practice of group guidance and counseling services. The research used descriptive quantitative method with total sampling technique, involving 33 Regular E/Stambuk 2022 counseling students as respondents. The instrument used was an online questionnaire which was analyzed with descriptive tests based on mean and standard deviation. The results showed that the level of student understanding of group guidance practice was mostly in the low category (52%), while understanding of group counseling showed a similar pattern, with 52% of respondents in the low category. This finding indicates the lack of students' ability to understand and practice the stages of group guidance and counseling. This study concludes that there is a need to strengthen practice-based learning, improve professional skills, and master supporting theories. The implications of the research include recommendations for curriculum development that focuses more on intensive practice and real situation-based training. It is recommended to integrate innovative learning methods to improve student understanding.